Productive and reproductive performance of dairy cattle of "zona da mata" region, Minas Gerais state, Brazil - Ferreira, Ademir de Moraes; de Sá, Wanderley ferreira; Villaça, Hermenegildo de Assis; de Assis, Airdem Gonçalves (Pesquisa Agropecuaria Brasileira, 1992)
Characterizing the traditional dairy farm of Minas Gerais State, Brazil, 50 dairy farms, which raise crosbred Holstein x Zebu cattle, were visited from July, 1981 to July, 1985. Management, nutrition, and, whenever possible, reprodutive data were observed. Females in reprodutive age, except heifers, were examined by rectal palpation. In the 3,408 examined cows, 47.9 were pregnant, where 16.2% were pregnant within 90 days from parturition and 83.8% had a days open mean of 240 days. Among the 594 cows found open before 90 days postpartum, 73.1% had inactive ovaries. The high incidence of anestrus was related to the bad body condition of the cows. Follicular cysts, mummified foetus, macerated foetus, uterine infections and repeat breeders cows were observed. Among the 2,249 of the cows in lactation, 31.1% were in lactation for more than ten months and 260 of then were open. These data indicate the low productive and reproductive performance of these herds. It severely affects the economic efficiency of the dairy operations in the region.
Keywords: crossbred; management; nutrition; zootechny; rectal palpation